Analisis Kriminologi dalam Tindak Pidana Pencurian Data Pribadi di Era Digital - Garnita, Camiliya Fakhriyah; Kuswandi, Kuswandi (Indonesian Journal of Law and Justice, 2025)
The The development of information technology in the digital age has increased the ease of access to data-based services, but it has also posed a serious threat in the form of personal data theft as a form of cybercrime. Personal data theft not only causes financial losses, but also has psychological and social impacts such as stress, anxiety, decreased trust in digital institutions, and damage to the victim's reputation. This study aims to analyze personal data theft from a criminological perspective by examining the driving factors, impacts, and weak data protection in Indonesia. The research method used is a qualitative approach through a literature study of regulations, criminological theories, and cases of data theft in digital and banking services. The results show that data theft is triggered by the perpetrators' economic motives, human error, malware attacks, social engineering, weak digital security systems, and low public literacy. In addition, the implementation of the Personal Data Protection Law (PDP Law) is considered suboptimal, thus failing to provide effective protection. This study concludes that personal data theft is a complex crime that requires regulatory strengthening, improved cybersecurity, and collaboration between the government, digital institutions, and the public to create a secure digital ecosystem.